Prevalencia de enteroparásitos en dos comunidades de Santa Rosa de Agua en Maracaibo, Estado Zulia, Venezuela 2006 - Calchi LC Marinella; Rivero de R Zulbey; Acurero O Ellen; Díaz A Iris; Chourio de L Glenis; Bracho M Angela; Maldonado I Adriana; Fernández G Bianca; Fernández L Mercy; González V Jesús; Villalobos P, Rafael (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Abstract: To determine the prevalence of enteroparasites in two communities of Santa Rosa de Agua, Zulia State, 216 faecal samples from both male and female individuals were analyzed, whose ages ranged from 1 month to 73 years. A direct coproparasitological test was performed on each faecal specimen using physiological saline solution, temporary coloration with Lugol's solution and Formol-Ether as a concentration method; to search for intestinal coccidian, Kinyoun tincture was applied. A statistical chi-square method was applied to analyze the results. A high percentage of individuals with parasites were observed (86.58%), predominantly polyparasitism (68.98%) associated with commensal and pathogenic species. Regarding the age group, the majority of those classified as young adults (20 to 39 years) were infected with parasites (20.83%). The ji-squared method demonstrated that there is no significant dependency between the presence of enteroparasites and sex (gender); when relating the age groups with parasite infections, a dependency between these two variables was found. The most frequent protozoan species were: Blastocystis hominis (64.07%), Entamoeba coli (26.73%), Giardia lamblia (22.45%). In terms of helminths, Trichuris trichiura (56.68%), Ascaris lumbricoides (44.09%), Hymenolepis nana (5,34%) had the highest incidence. It has been found that both communities in Santa Rosa de Agua show a high prevalence of parasites, a situation previously observed in some other communities with low or poor socio-sanitary and hygienic conditions. Resumen: Para determinar la prevalencia de enteroparasitos en dos comunidades de Santa Rosa de Agua en el Estado Zulia, se analizaron 216 muestras fecales de individuos de ambos sexos, con edades comprendidas entre 1 mes a 73 años. A cada espécimen fecal se le realizó un examen coproparasitológico directo con SSF (0,85%), coloración temporal de lugol y método de concentración de Formol-Éter; para la búsqueda de coccidios intestinales se aplicó la tinción de Kinyoun. Se observó un elevado porcentaje de individuos parasitados (86,58%), en donde predominó el poliparasitismo (68,98%) con asociación entre especies comensales y patógenas. En cuanto al grupo etario, el estrato de los adultos jóvenes (20 a 39 años) resultó mayormente parasitado (20,83%). A través del Ji (x2) no se observó diferencia significativa entre las enteroparasitosis y sexo; al relacionar los grupos etarios con las infecciones parasitarias, si hubo diferencia entre éstas dos variables. Las especies de protozoarios más prevalentes fueron: Blastocystis hominis (64,07%), Entamoeba coli (26,73%), Giardia lamblia (22,45%). Dentro de los helmintos: Trichuris trichiura (56,68%), Ascaris lumbricoides (44,09%), Hymenolepis nana (5,34%) ocuparon los primeros lugares. Las comunidades estudiadas de Santa Rosa de Agua presentan elevada prevalencia por enteroparásitos, situación similar a la observada en otras comunidades con condiciones socio-sanitarias e higiénicas deficientes.